2010
DOI: 10.1292/jvms.10-0185
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ku80 in Living Hamster Cells with DNA Double-Strand Breaks Induced by Chemotherapeutic Drugs

Abstract: ABSTRACT. A variety of chemotherapeutic drugs, e.g., etoposide and bleomycin, are widely used in clinical practice to treat many types of animal malignancies. In the clinical situation, cellular resistance to chemotherapy is a significant component of tumor treatment failure. A variety of DNA repair factors, e.g., Ku80, might be a key contributor to chemoresistance to anticancer agents. In both cancer and normal cells, Ku80 plays a key role as a sensor of DNA double-strand break (DSB) induced by treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…In hamster cells, Ku70/Ku80 heterodimer accumulation at DSBs produced using a 405-nm laser starts immediately after irradiation [18], strongly supporting the idea that the heterodimer of Ku70 and Ku80 is a sensor of DSBs in the nuclei. Most recently, we have reported that Ku80, in contrast to H2AX, is highly mobile in the nuclei of hamster cells and that the mobility of a major portion of Ku80 is not affected by DNA DSBs produced by treatment with antitumor drugs [19]. Ku70 is mainly detected in the nuclei of normal human diploid lung fibroblasts, e.g., TIG-3 and MRC-5, and human cancer cells, e.g., HeLa and MCF-7 cells [11,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In hamster cells, Ku70/Ku80 heterodimer accumulation at DSBs produced using a 405-nm laser starts immediately after irradiation [18], strongly supporting the idea that the heterodimer of Ku70 and Ku80 is a sensor of DSBs in the nuclei. Most recently, we have reported that Ku80, in contrast to H2AX, is highly mobile in the nuclei of hamster cells and that the mobility of a major portion of Ku80 is not affected by DNA DSBs produced by treatment with antitumor drugs [19]. Ku70 is mainly detected in the nuclei of normal human diploid lung fibroblasts, e.g., TIG-3 and MRC-5, and human cancer cells, e.g., HeLa and MCF-7 cells [11,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were grown in a monolayer culture in DMEM (Nissui Seiyaku Co., Tokyo, Japan) supplemented with 10% fetal bovine serum and were maintained in a humidified incubator at 37°C under 5% CO 2 . Transient transfections were performed in Ku70-/-cells using FuGene6 (Roche Diagnostics K.K., Indianapolis, IN, U.S.A.) as described previously, and the cells were cultured for 2 days and then monitored using an FV300 confocal laser scanning microscope (Olympus, Tokyo, Japan) as previously described [18,19].…”
Section: Mice Cell Lines Cultures and Transfectionmentioning
confidence: 99%
See 3 more Smart Citations